An Examination of Women's Self-Presentation, Social Physique Anxiety, and Setting Preferences during Injury Rehabilitation. (12th March 2017) - Driediger, Molly V.; McKay, Carly D.; Hall, Craig R.
Abstract : Objectives . This study investigated whether women experience self-presentational concerns related to rehabilitation settings and explored preferences for characteristics of the social and physical treatment environment in relation to women's Social Physique Anxiety (SPA). Methods . Two cross-sectional studies were conducted. In Study 1, female undergraduate students (n = 134 ) completed four questionnaires (Social Physique Anxiety Scale; three bespoke questionnaires assessing self-presentation in rehabilitation and social and physical environment preferences) with respect to hypothetical rehabilitation scenarios. Study 2 recruited injured women who were referred for physiotherapy (n = 62 ) to complete the same questionnaires regarding genuine rehabilitation scenarios. Results . Women with high SPA showed less preference for physique salient clothing than women with low SPA in both hypothetical (p = 0.001 ) and genuine settings (p = 0.01 ). In Study 2, women with high SPA also preferred that others in the clinic were female (p = 0.01 ) and reported significantly greater preference for private treatment spaces (p = 0.05 ). Conclusions . Self-presentational concerns exist in rehabilitation as in exercise settings. Results indicated inverse relationships between women's SPA and preference for the presence of men, physique-enhancing clothing, and open-concept treatment settings. Future studies to determine the effect of self-presentational concerns on treatment adherence are needed.